Analisis Peran Guru Dalam Motivasi Siswa Kelas V SDN Sarirejo 03 - Faradine, Maulina Rizky; Rondli, Wawan Shokib; Riswari, Lovika Ardana (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2023)
The purpose of this study was to find out how the role of the teacher in increasing student learning motivation in learning at SDN Sarirejo 03 Pati Regency. This study uses a qualitative approach with a case study type of research. This research will be conducted at SD Negeri Sarirejo 03 by taking teachers and students as research subjects. The results of this study indicate the teacher's role in motivating student learning to learn optimally. The role of the teacher includes the teacher as a facilitator, the teacher provides learning facilities with the help of textbooks, LKS besides that the teacher makes use of the surrounding environment or technological developments, the teacher as a motivator the teacher motivates by giving rewards such as starboards, if there are students who are not enthusiastic about learning the teacher visits the place students sit, the teacher as a trigger, the teacher uses scientific learning methods and problem solving, and the teacher as an inspiration, the teacher creates a conducive atmosphere by designing rules and prohibitions and sanctions that have been agreed upon by the teacher and students.